Maqashid Al-Syariah Dalam Perilaku Ekonomi - Ma’zumi Ma’zumi (FEB Universitas Sultan Ageng Tirtayasa, 2019)
Islam is a system of life. Economy is a subsystem in the system of life. The quality of the economic subsystem depends on the building of Aqidah, Shari'ah, and morality, which is the pillar of the system to carry out life activities in its interactions related to assets (mu'amalah al-maliyah), and interactions that are not related to property (mu’amalah ghairu maliyah) Economic activities are included in the mu'amalah al-maliyah. Economic activity in the view of Islam is a recommendation and demand for life that has a dimension of worship, even an order to carry out productive activities for fulfilling the needs of dharuuriyyaat (primary), haajiyyaat (secondary) and tahsiiniyyaat (tertiary). Maqashid al-syariah (the goal of sharia) in the reality of economic behavior is a productive activity for fulfilling needs that can maintain faith (din), humans (nafs), intellect (aqal), descendants (nasl), and wealth (maal) . ”The five things are the synthesis of system buildings in a balanced and harmonious survival. In the process, it is practically a sign for economic actors in the framework of just and prosperous socio-economic development, through zakat instruments, usury prohibition, anti-monopoly as social security and the role of government.